Tunnels of blood / 3 - Shan, Darren (Cirque du freak, 2002)
Darren, Evra, and Mr. Crepsley leave the Cirque Du Freak and get a taste of the city, but when corpses drained of blood are discovered, Darren and Evra must confront a dangerous creature of the night.